2015
DOI: 10.1038/jp.2015.22
|View full text |Cite
|
Sign up to set email alerts
|

Growth and developmental outcome of infants with in-utero exposure to methadone vs buprenorphine

Abstract: Exposure to maternal methadone dose in excess of 100 mg is associated with a reduction in infant head circumference when compared with buprenorphine or lower dose methadone, and may have a negative impact on motor skill development during early infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 15 publications
1
29
0
5
Order By: Relevance
“…This association persisted for cognition up to 2 years of age (MDI 99.2 vs 82.0, p <0.01). Bier et al reported MDI scores in the normal range at 4 months of age, in a cohort of 165 methadone‐exposed infants, with no difference between those infants exposed prenatally to either low dose (<100mg/d) or high dose (≥100mg/d) methadone.…”
Section: Resultsmentioning
confidence: 99%
“…This association persisted for cognition up to 2 years of age (MDI 99.2 vs 82.0, p <0.01). Bier et al reported MDI scores in the normal range at 4 months of age, in a cohort of 165 methadone‐exposed infants, with no difference between those infants exposed prenatally to either low dose (<100mg/d) or high dose (≥100mg/d) methadone.…”
Section: Resultsmentioning
confidence: 99%
“…Arlettaz et al, 3 in a retrospective study of 86 newborns exposed to methadone, reported a 13% incidence of HC less than the third percentile, but 62% were also exposed to additional drugs, primarily cocaine. Bier et al 11 reported significantly smaller HC z scores for neonates exposed to a high dose of methadone (>100 mg daily dose) compared with newborns exposed to a low dose of methadone or buprenorphine. Additionally, in a few small studies, researchers have reported smaller brain volumes and abnormal white matter development in older children (ages 9-14) who received treatment of NAS after birth compared with controls, suggesting that children may not experience "catch-up" growth in HC through early adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to compare the effects of different prenatal MAT regimens (methadone vs. buprenorphine and dose levels) on neurodevelopment have yielded inconsistent results. For example, the MOTHER study [16] and a retrospective cohort in Massachusetts [36] found no association, while a prospective cohort in Australia found differences in visual evoked potentials between methadone- vs. buprenorphine-exposed infants at 4 months of age, which did not persist to a 36months evaluation [37]. While there are some indications that brain function may be altered by prenatal exposure to methadone vs. buprenorphine in infancy, the small number of studies to examine this have also reported normalization of the assessed sensory function between 6 and 36 months of age [35, 37].…”
Section: Discussionmentioning
confidence: 99%